Health Literacy in patients with angina pectoris disease referred to selected hospitals in of Tehran - Abozar Ejadi; Somaye Javanmardnejad; Nahid Rejeh; Majideh Heravi- Karimooi; Seyed Davood Tadrisi (Mashhad University of Medical Sciences, 2020)
Background and Objective: Angina pectoris is one of the most common among heart diseases. Low health literacy is associated with a high prevalence of chronic diseases, including cardiovascular disease. Considering the significant burden of heart disease, improving the level of health literacy of individuals can play a decisive role in the prevention and treatment of these diseases and saving resources. The aim of this study was to investigate the level of health in patients to Angina pectoris, who referred to selected hospitals in Tehran. Materials and Methods:This study is a descriptive-analytical study that was performed on 405 patients with angina referred to the heart clinics of selected hospitals in Tehran in 2017. Patients were selected by convenience sampling. Data were collected using demographic questionnaires, Health Literacy of Iranian Adults (HELIA) and analyzed by descriptive and inferential statistics and Anova with SPSS software version 20. Results:: The mean age of the patients was 53.08. The average score of health literacy of patients with angina pectoris (63.77 ± 15.44) is based on the fact that it can be said that the subjects in terms of health literacy were not at a sufficient level. The results of Anova statistical test showed There is a statistically significant relationship between health literacy level and age variables, education level, employment status, income level, duration of heart disease and heart disease and ways of obtaining medical information (p <0.05). Conclusion: The findings showed that patients need more explanation to understand and use health information and need to spend more time acquiring information in a simpler and more understandable language.